Urban household's behaviour towards domestic waste recycling, Shah Alam, Selangor / Nurul Rif'ah Afiqah Abd Rauf - Abd Rauf, Nurul Rif'ah Afiqah (2023)
Solid waste management has become one of the challenging issues and problems faced by local governments in developing countries worldwide, and poor waste management can raise costs and harm the environment. Thus, many countries encourage recycling to protect the environment and improve waste management. However, domestic waste management during the COVID-19 pandemic, a scarcity of land for landfill, and low household recycling involvement affect waste recycling in Malaysia. Therefore, this study attempts to construct a Human Behaviour Framework for urban households in domestic waste recycling. The researcher examines the theory and factors of household behaviour, investigates the practice of domestic waste recycling, analyses the recycling factors and practices, and proposes the human behaviour framework for domestic waste recycling. This study utilised Site Observation, Questionnaires, Expert Interviews, and Focus Group Discussion (FGD). The 360 urban households in Seksyen 2, 6, 7, 8, 10 and 11, Shah Alam, were selected using Stratified Random Sampling and analysed using Statistical Package Social Sciences (SPSS). It was found that urban households’ domain factors in recycling behaviour influence their intention to recycle, and the efficiency of waste recycling mechanisms and systems reflects their involvement in waste segregation and domestic waste recycling practises. The study indicated five (5) behavioural factors in recycling behaviour: Knowledge (K), Attitude (A), Spatial and Physical (SP), and Situational (ST) factors. Knowledge and attitude have the most negligible impact compared to spatial, physical, situational, and social factors. People recycle if they have access to waste facilities and recycling centres, if garbage offenders are prosecuted, and if the community recycles and separates waste. Hence, the study suggests improved recycling policies and strategies through the proposed Human Behaviour Framework (HBF).